UPAYA GURU DALAM MEMBERIKAN MOTIVASI BELAJAR KEPADA SISWA BERKEBUTUHAN KHUSUS (TUNANETRA) DI SLB NEGERI 2 LOMBOK TENGAH - Samsul Bahri (Universitas Islam Negeri Mataram, 2022)
This study aims to describe the teacher's efforts in providing learning motivation to students with special needs (visually impaired) at SLB Negeri 2 Central Lombok and the obstacles faced by teachers in providing learning motivation to students with special needs (visually impaired) at SLB Negeri 2 Central Lombok. The approach used in this study is a qualitative derscriptive approach, the Data Collection Method in this study uses observation, interview, and documentation methods. Data analysis techniques Data analysis can be divided into two, namely: qualitative data analysis, descriptive analysis. The steps used in analyzing data are: data education, data presentation, verification. data reduction, data display, verification. Meanwhile, checking the validity of the data is carried out using a credibility test, transferability test, dependability test, confirmability test. The results of this study show that: (1) upay.